First Man : The Life of Neil A. Armstrong - Hansen, James R. (New York : Simon & Schuster, 2005)
On July 20, 1969, the world stood still to watch 38-year-old American astronaut Neil A. Armstrong become the first person ever to step on the surface of another heavenly body. Upon his return to Earth, Armstrong was celebrated for his monumental achievement. He was also--as NASA historian Hansen reveals in this authorized biography--misunderstood. Armstrong's accomplishments as an engineer, a test pilot, and an astronaut have long been a matter of record, but Hansen's access to private documents and unpublished sources and his interviews with more than 125 subjects (including more than fifty hours with Armstrong himself) yield the first in-depth analysis of this elusive, reluctant hero. Hansen recreates Armstrong's flying career, from his combat missions over North Korea to his transatmospheric flights in the rocket-powered X-15 to the first-ever docking in space. For a pilot who cared more about flying to the Moon than he did about walking on it, Hansen asserts, Armstrong's storied vocation exacted a dear personal toll, paid in kind by his wife and children.--From publisher description.
I: An American genesis -- The strong of arm -- The strong of spirit -- II: Tranquility base -- First child -- The virtues of Smallville -- Truth in the air -- Aeronautical engineering 101 -- III: Wings of gold -- Class 5-49 -- Fighter Squadron 51 -- Fate is the hunter -- The ordeal of eagles -- IV: The real right stuff -- The research pilot -- Above the high desert -- At the edge of space -- The worst loss -- Higher resolve -- I've got a secret -- V: No man is an island -- Training days -- In line for command -- Gemini VIII -- The astronaut's wife -- For all America -- VI: Apollo -- Out of the ashes -- Wingless on luna -- Amiable strangers -- First out -- Dialectics of a moon mission -- VII: One giant leap -- Outward bound -- The landing -- One small step -- Return to earth -- For all mankind -- VIII: Dark side of the moon -- Standing ground -- To engineer is human -- The astronaut is icon -- Into the heartland.
Includes bibliographical references (p. 719-738) and index.
Accelerated Reader AR
Keywords: Armstrong, Neil, -- 1930-; Project Apollo (United States); Astronauts -- Biography -- United States; Space flight to the moon